2021
DOI: 10.1038/s41598-021-91685-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional study of the clinical characteristics of French primary care patients with COVID-19

Abstract: The early identification of patients suffering from SARS-CoV-2 infection in primary care is of outmost importance in the current pandemic. The objective of this study was to describe the clinical characteristics of primary care patients who tested positive for SARS-CoV-2. We conducted a cross-sectional study between March 24 and May 7, 2020, involving consecutive patients undergoing RT-PCR testing in two community-based laboratories in Lyon (France) for a suspicion of COVID-19. We examined the association betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Many also presented with nonspecific symptoms like headache, fatigue and myalgia. Some were rare like rash or frostbite [7][8][9]. Although it is crucial to have better understanding of signs and symptoms of covid 19 infection in primary care setting it is also found that valid correlation of symptoms with the diagnosis requires standard tools [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many also presented with nonspecific symptoms like headache, fatigue and myalgia. Some were rare like rash or frostbite [7][8][9]. Although it is crucial to have better understanding of signs and symptoms of covid 19 infection in primary care setting it is also found that valid correlation of symptoms with the diagnosis requires standard tools [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is crucial to have better understanding of signs and symptoms of covid 19 infection in primary care setting it is also found that valid correlation of symptoms with the diagnosis requires standard tools [10]. Clinical Investigations, including inflammatory markers and radiological tests to rule out potential life-threatening complication like acute respiratory distress syndrome and multisystem inflammation were found to be essential in determining the severity index in the primary care settings like the approach in hospitals and other inpatient facilities [5][6][7]. The outcome of management and control was quite inspiring at the primary health care centers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations